Evaluation of the Nutritional Quality, Bioactive Compounds, and Antioxidant Activity of Moringa oleifera Leaf Extract - Mikail, Tasiu Abdulmumin; Sagir Yusuf Ismail; Amina Lawan Abubakar; Yunusa Abdulmumin; Ibrahim Ahmad Muhammad; Murtala Muhammad; Hauwa Ibrahim Danjaji (Sahel Journal of Life Sciences FUDMA, 2025)
This study was conducted to evaluate the proximate and mineral compositions, phytochemical content, and antioxidant activity of Moringa oleifera leaf extract to determine its nutritional quality and medicinal attributes. The proximate, mineral, and phytochemical contents were evaluated using standard methods. The result of proximate compositions revealed that Moringa oleifera leaves contain ash (10.12±0.3), moisture (7.10±0.1), protein (19.05±0.2), fat (2.03±0.01), fiber (13.5±0.02), and carbohydrates (48.20±1.02). This showed that Moringa oleifera leaves are rich in proteins and fiber and have low moisture and high ash contents. The results of the mineral analysis indicated that the leaves of Moringa oleifera are rich in minerals, the concentration of the mineral elements in μg/g are iron (3.15±0.01), potassium (5.10±0.03), calcium (6.24±0.01), zinc (1.14±0.001), magnesium (4.62±0.02), and copper (2.02±0.03). The ethanolic extract of Moringa oleifera leaves was analyzed for phytochemicals, the results indicated the presence of alkaloids (3.31±0.03 g/100g), flavonoids (5.01±0.1 g/100g), glycosides (0.25±0.001 g/100g), anthraquinones (3.03±0.05 g/100g), terpenoids (5.45±0.01 g/100g), tannins (2.09±0.02 g/100g) and phenols (13.89±0.1 g/100g). The DPPH and ABTS radical scavenging assay showed that Moringa oleifera leaf extract can scavenge free radicals. However, the highest inhibition was 90.98 % for DPPH and 95.14% for ABTS, all at 100 mg/ml. The high antioxidant activity observed could be attributed to the high concentration of bioactive compounds, especially phenols and flavonoids. Based on these findings, it could be inferred that Moringa oleifera leaves could be used as a source of nutrients and bioactive compounds that can be used in the management and treatment of chronic diseases.